Implications of mangrove diversity on planted land area mangrove forest Pematang Kuala Serdang Bedagai - Hendrawan, Dian; Warsodirejo, Pandu Prabowo (Universitas Malikussaleh, 2022)
Pematang Kuala Village is one of the villages in the Mengkudu Bay District which has an area of almost 80% of which is mangrove forest. The existence of the Mangrove Forest is very important in addition to being a source of livelihood for the population, most of whom are fishermen, its function is also to protect coastal areas from increasingly severe coastal abrasion. The mangrove forest in this village is a mangrove forest that is managed jointly by the community to meet the needs of the community. Most of the village areas that are not mangrove forests are now converted into oil palm plantations or ponds which can damage mangrove ecosystems and coastal areas. This study aims to analyze the level of abundance, biomass, diversity and potential of fauna, distribution patterns of mangrove plants and fauna as well as the effect of conversion of mangrove diversity and the components contained therein on planted areas in the mangrove area to obtain data in Pematang Kuala Village, Teluk Mengkudu District, Serdang Be different. This research was conducted from January to March 2022. The study used data analysis techniques for diversity and abundance of the Shanon Winner index. There were 11 Mangrove species in total which were obtained at 3 research sites. Each research station is divided into 3 data collection, namely Trees, Trunks, and Seedlings. The highest diversity index was found in trees at station 1, which was 2.52%. and the lowest index is station 2 tree type was 0.15%.